UPAYA PENINGKATAN SEMANGAT KERJA KARYAWAN MELALUI KEPEMIMPINAN DAN MOTIVASI PADA PT.BPR PEDUNGAN (Study Pada PT. BPR Pedungan Denpasar Bali) - Putu Sintia Wulandar; I Made Hedy Wartana (Journal Research of Management, 2020)
Employee morale is a very important thing in supporting the achievement of an organization's goals, if morale is high it tends to be able to finish work well andquickly, conversely if morale is low then the work will be less well done and employees become dissatisfied. Employee morale can be measured one of them by looking at the percentage of employee absenteeism at work. This study aims to determine the effect of leadership on employee morale, the effect of motivation on morale, to find out how much the contribution of influence between leadership and motivation on employee morale, and also to find out which variables are more dominant on the morale of employees of PT. BPR Pedungan. The respondents of this study were employees of PT. BPR Pedungan, amounting to 91 people. The analysis technique used is multiple linear regression analysis. The multiple regression equation is: Y = 3.380 + 0.464 X1 + 0.450 X2. T test is used to determine the effect of independent variables on the dependent variable partially. Based on the results of the analysis note that leadership and motivation have a positive and partially significant effect on employee morale. Where leadership has a t-count value (4,559)> t-table (1,662), motivation has t-count (4,063)> t-table (1,662). Contributions contributed by leadership (X1) and motivation (X2) to employee morale (Y) at PT.BPR Pedungan are 80.8%, while the remaining 19.2% is influenced by other factors not analyzed in this study such as communication and work discipline. Leadership (X1) gives a more dominant influence compared to motivation (X2) on employee morale (Y) at PT. Rural BPR, where the value of β for the leadership variable is 0.488 and motivation is 0.435. Based on the results of the study, it can be suggested by the leadership of PT. BPR Pedungan always pays attention to leadership and motivation because together these two variables are able to increase Employee Morale at PT.BPR Pedungan.